SOCIAL ROLE CONFLICT AND RELIGIOUS HEGEMONY: SOCIAL BACKGROUND IN ANNA KARENINA NOVEL BY LEO TOLSTOY - Adila, Siti Syahrah; Yusuf, Faidah; Nahdhiyah, Nahdhiyah (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2020)
Using the sociological theory of literature, the researchers agreed to study Leo Tolstoy's novel Anna Karenina, which will bring on connections in the social arts. In a descriptive qualitative, the investigator uses note sheets as analysis methods to evaluate knowledge to illustrate how the tension of social significance and religious hegemony arise. After an overview of the results, Leo Tolstoy in Anna Karenina Novel concludes his research finding on the social conflict. The social role and religious hegemony were expected. A social role is also a pit for social participants in their unconsciousness, such that conflict becomes an inseparable aspect and obstacles between groups in the social order, and religious hegemony, which in human behavior is manifested as an important role in the social realm of humans, religious instruction. Religion is a reference to the social and moral life.